2013
DOI: 10.1123/krj.2.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Powering Adherence to Physical Activity by Changing Self-Regulatory Skills and Beliefs: Are Kinesiologists Ready to Counsel?

Abstract: There are multiple avenues to gain health promoting and disease preventing benefits of physical activity (PA) but nonadherence makes health benefits short-lived. Gains obtained through structured exercise training and therapy quickly decay once participants leave programs. Scientific position statements underscore cognitive-behavioral strategies (CBS) as an essential intervention component to increase and maintain PA and recommend transfer of CBS knowledge to practice. Our review of reviews indicates high qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
4
11
0
Order By: Relevance
“…Examples of this include the opportunities to practice their motivational interviewing skills, as well as guide residents in learning self-regulatory skills like action planning and self-monitoring, that would help the resident increase their own physical activity. These regulatory skills are commonly identified as key factors in physical activity adherence, and are a skill that many Kinesiology students are not exposed to during their training (Brawley et al, 2013). Anecdotally, through the reflections, students reported having to push themselves, as talking with strangers about physical activity is not something they had been exposed to yet in their schooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of this include the opportunities to practice their motivational interviewing skills, as well as guide residents in learning self-regulatory skills like action planning and self-monitoring, that would help the resident increase their own physical activity. These regulatory skills are commonly identified as key factors in physical activity adherence, and are a skill that many Kinesiology students are not exposed to during their training (Brawley et al, 2013). Anecdotally, through the reflections, students reported having to push themselves, as talking with strangers about physical activity is not something they had been exposed to yet in their schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Common compenents of health coaching include motivational interviewing, and teaching behavior change skills such as goal setting, and selfmonitoring (Olsen & Nesbitt, 2010). It has been suggested that there is a need for Kinesiology students to learn and practice these skills of motivational interviewing and behavior change as it is not currently common among Kinesiology programs (Brawley, Gierc, & Locke, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature on the knowledge of training for health promotion professionals (Brawley, Gierc, & Locke, 2013;Davidson, 2008). A panel of nationally recognized health education leaders identified "communication" as one of the nine areas of competency that health educators need but often lack (Allegrante, Moon, Auld, & Gebbie, 2001).…”
Section: Academic Training For Health Promotion Professionalsmentioning
confidence: 99%
“…Studies investigating habit formation are sparse, use small sample sizes [24,25], and rarely focus on strategies required to maintain change [26]. Limited guidance for helping people to maintain behaviour change may, in part, explain poor long-term adherence to programmes [12,18,19,21,[25][26][27][28][29][30][31].…”
mentioning
confidence: 99%